Imaging Spatial Variations of Optical Bandgaps in Perovskite Solar Cells. Issue 7 (14th December 2018) - Chen, Boyi; Peng, Jun; Shen, Heping; Duong, The; Walter, Daniel; Johnston, Steve; Al‐Jassim, Mowafak M.; Weber, Klaus J.; White, Thomas P.; Catchpole, Kylie R.; Macdonald, Daniel; Nguyen, Hieu T.
Abstract: A fast, nondestructive, camera‐based method to capture optical bandgap images of perovskite solar cells (PSCs) with micrometer‐scale spatial resolution is developed. This imaging technique utilizes well‐defined and relatively symmetrical band‐to‐band luminescence spectra emitted from perovskite materials, whose spectral peak locations coincide with absorption thresholds and thus represent their optical bandgaps. The technique is employed to capture relative variations in optical bandgaps across various PSCs, and to resolve optical bandgap inhomogeneity within the same device due to material degradation and impurities. Degradation and impurities are found to both cause optical bandgap shifts inside the materials. The results are confirmed with micro‐photoluminescence spectroscopy scans. The excellent agreement between the two techniques opens opportunities for this imaging concept to become a quantified, high spatial resolution, large‐area characterization tool of PSCs. This development continues to strengthen the high value of luminescence imaging for the research and development of this photovoltaic technology. Abstract : A fast, nondestructive, camera‐based method to capture optical bandgap images of perovskite solar cells with micrometer‐scale spatial resolution is developed. This technique allows for the probing of relative variations in optical bandgaps across various solar cells, and for the resolution of bandgap inhomogeneity within the same device due to material degradation and impurities. The results are independently confirmed with other optical‐based techniques.